Production of Acetoin and Diacetyl by the Genus Salmonella - Garibaldi, J. A. (1970)
Members (all 42 tested) of the genus Salmonella, although Voges-Proskauer-negative when grown on MR-VP Medium, produce abundant quantities of acetoin or diacetyl, or both, when cultured on a minimal medium containing 1% glucose. The designation that the genus Salmonella does not produce acetoin should be re-examined.